Application Statement Analysis Conversation of the Murder Case at the Makassar District Court (Forensic Linguistics) - Jahara; Munirah; Andi Sukri Syamsuri (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This research is important because the type of language forensic research is still very minimal. The next reason is more on the interest and interest of researchers in understanding language forensics. Research aims; (1) conduct a forensic linguistic study through the application of statement analysis on the Conversation of the Murder Case Trial at the Makassar District Court; and (2) find out what are the contributions of applied forensic linguistics statement analysis on the Conversation of the Murder Case Trial at the Makassar District Court. This research is study descriptive Qualitative research with forensic linguistics approach applies statement analysis to the Conversation of the Murder Case Session at the Makassar District Court. The data of this research is the conversation of the murder case trial at the Makassar District Court and the source of the data is the recorded conversation of the murder case trial at the Makassar District Court. Data collection techniques are; recording technique, listening technique, and note-taking technique. Analysis qualitative data is inductive, namely an analysis based on the data obtained. Based on the results of the study, it was concluded that; (1)analysis results in application statement analysis In the conversational language forensics of the murder case trial at the Makassar District Court, seven patterns of statement analysis criteria were found, namely; (a) the use of terms of action phrases; (b) the use of special meaning phrases; (c) perception builder; (d) verb euphemisms; (e) use of pronouns; (f) excessive “I”; and (g) time span patterns; and (2) the results of the application analysis statement analysis In forensics the conversational language of the murder case trial at the Makassar District Court can make an important contribution in the form of forensic results that can be a means of confirming factual information and can be used as a tool to legitimize criminal events. These two forms of contribution can be academic proposals for judges to enforce the law fairly and wisely.